Numerical Investigation of Third‐Body Behavior in Dry and Wet Environments under Plane Shearing. Issue 8 (24th May 2016) - Pieper, Christoph; Oschmann, Tobias; Markauskas, Darius; Kempf, Andreas; Fischer, Alfons; Kruggel‐Emden, Harald
Abstract: A coupled discrete element method and computational fluid dynamics (DEM‐CFD) approach to model and assess third‐body behavior in dry and wet environments under plane shearing is presented. DEM is used to model the granular media, while the fluid side of the system is simulated with CFD, which is based on the finite volume method. The applied model is extended to consider buoyancy as well as lubrication effects. The third body is confined and compressed between two walls, which are sheared in opposite direction with a constant velocity. The influence of different shear velocities, fluid viscosities, and gravity orientations on particle and fluid rheology is investigated. Obtained results of both dry and lubricated systems are compared regarding velocity and porosity distribution across the gap, sliding friction, and particle interaction. Abstract : Thin particle layers, called third‐body or tribomaterial, develop under severe plastic deformation of the near‐surface solid‐body layers. A numerical study of the third‐body behavior in wet and dry environments has been conducted based on the coupled discrete element method‐computational fluid dynamics approach. The applied model was extended to consider buoyancy as well as lubrication effects.